Work Incentives for Sectoral Research Institute Researchers - O. N. Rimskaya; S. N. Naumenko (Ekonomika Nauki)
The article considers issues of researchers’ work assessment of sectoral research institutes in the Russian Federation. The authors investigate the advantages and disadvantages of the existing system of scientometric indicators with relation to the researchers’ publication activity increase. Practical solutions are proposed to harmonize the internal and external motivation of the researchers’ work of the sectoral research institute in order to ensure the effectiveness of their scientific activities, the implementation of key indicators of the effectiveness of scientific work and to promote the economic and innovative effect of the institute activities. The authors proposed a conceptual system for stimulating the work of researchers through authorship in scientific publications and evaluated its effectiveness. The scientific novelty lies in the development of a system of incentives for authorship in scientific publications to employees of the Railway Research Institute. The practical significance of the study lies in the possibility of applying the incentive system in many sectors of the modern economy.